Development and survival of Theileria parva parva in Rhipicephalus appendiculatus exposed in the Trans-Mara, Kenya - Young, A.S.; Leitch, L.; Morzaria, S.P.; Irvin, A.D.; Omwoyo, P.L.; Castro, J.J. de (Cambridge University Press, 1987)
Nymphal Rhipicephalus appendiculatus (Trans-Mara) were fed on a steer infected with a Theileria parva parva (Kilae 1) stock isolated from an indigenous steer in the Trans-Mara Division, Kenya, which had a high piroplasm parasitaemia. A total of 5000 engorged nymphs which had dropped on one day were enclosed in elongated nylon bolting silk tubes in groups of 200–300 and were transported immediately to the Trans-Mara where they were suspended vertically in the grass cover with one end touching the ground. Over 98% of the nymphs moulted into adult ticks and 50% moult occurred by day 28 after exposure. The ticks showed over 80% survival up to 308 days post-exposure but thereafter showed a marked mortality so that only 22·5 % of the ticks were alive after 439 days. Theileria parasites were detected in the salivary glands by day 35 post-exposure and infection rates and levels increased markedly between 180 and 235 days post-exposure. Thereafter, the infection rates and levels generally decreased. Groups of ticks were triturated and the resultant supernatant fluid inoculated into pairs of susceptible cattle, and these proved infective from day 44 to 145 after exposure. Three subsequent attempts to induce infections with supernatant fluid were unsuccessful. From 294 days after exposure, groups of 50 ticks were applied to cattle and caused lethal T. p. parva infections up to 439 days post-exposure. Climatic observations showed a relatively even monthly rainfall as well as mean maximum and minimum monthly temperatures. Clean nymphal R. appendiculatus were applied to a steer infected by adult ticks exposed for 405 days and the resultant adults were incubated at 37 °C for 6 days. Supernatant fluid produced from these ticks caused a lethal T. parva infection in a susceptible steer.